MENINGKATKAN PEMAHAMAN SEJARAH SISWA DENGAN MENGGUNAKAN MODEL DISCOVERY LEARNING PADA MATERI PERANG DINGIN MATA PELAJARAN SEJARAH - Rudiana, Aen (Balai Diklat Keagamaan Bandung, 2023)
Historical comprehension needs to be possessed by everyone from an early age in order to know and understand the meaning of past events, without this understanding skill, historical learning loses its spirit. History can be used as a basis for attitudes in facing present reality and determining the future. Based on the results of a pre-survey conducted at Madrasah Aliyah Negeri 2 Ciamis for the 2023/2024 academic year, the ability to understand history in class XII IPS 1 is quite low. Therefore, the purpose of this study is to determine the ability to understand the history of man 2 Ciamis students in material from the cold war using a discovery learning model. Based on the results of cycle 1 (one) and cycle 2 (two) in the field of attitude, there was an increase from cycle 1 (one) to cycle 2 (two) by 79%. Meanwhile, in the value of knowledge from cycle 1 (one) to cycle 2 (two) there was an increase of 44%. Therefore, students in studying history must understand more deeply the material studied. The benefits that can be drawn from this paper will make it easier for students to study various historical events more meaningfully so that the saying